Polypyrrole modified magnetic reduced graphene oxide composites: synthesis, characterization and application for selective lead adsorption. Issue 30 (5th May 2020) - Liu, Zhanmeng; Gao, Zhimin; Xu, Lichun; Hu, Fengping
Abstract : Compared to Fe3 O4 /rGO, the PPy-FG composites showed desirable adsorption capacity and selectivity for Pb(ii ) from water. Abstract : To enhance the ability to remove lead from water, polypyrrole modified magnetic Fe3 O4 /reduced graphene oxide composites (PPy-FG) were prepared via in situ polymerization and employed for the Pb(ii ) adsorption. The physicochemical structure and adsorption mechanism of the prepared magnetic PPy-FG were studied via vibrating sample magnetometer, X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, Brunauer–Emmett–Teller analysis, and X-ray photoelectron spectroscopy. The effects of several factors on Pb(ii ) adsorption were evaluated, including pH value, temperature, and competitive ions. Under the optimal conditions (pH 5 and 298 K), the maximum adsorption capacity of PPy-FG was 93.2 mg g −1 giving an improvement of 31% over that of 71 mg g −1 for Fe3 O4 /reduced graphene oxide (Fe3 O4 /rGO). Moreover, the experimental data were well fitted with the Langmuir adsorption model and the pseudo-second-order kinetics model, indicating that the adsorption process was mainly a monolayer chemical adsorption. Thermodynamic studies revealed a spontaneous and endothermic adsorption process. The selective adsorption of Pb(ii ) by PPy-FG is superior to that of Fe3 O4 /rGO in the presence of similar metals in the same medium. In addition, the adsorption performance of PPy-FG showed great potential in the remediation of heavy metal contaminated water through using its magnetic properties and excellent affinity for heavy metals.